Formação e mineralização de substâncias húmicas desde a decomposição de macrófitas aquáticas em reservatórios tropicais com diferentes graus de trofia - Souza, Brayan Pétrick de (2015)
The decomposition of aquatic macrophytes is important for understanding the cycling of elements and organic matter in aquatic ecosystems. The decomposition rate is driven by biotic and abiotic factors. Thus, the aim of this study was to analyze the effects of trophic status and detritus quality on the humification and mineralization of aquatic plants. The study was conducted in two tropical reservoirs (RJ/Brazil) with different trophic statuse (Lajes Reservoir: oligo-mesotrophic; Vigário Reservoir: eutrophic). In each reservoir were incubated (litter bags), during the dry season, five species of aquatic plants (Eichhornia crassipes (Mart.) Solms., Pistia stratiotes (L.), Sagittaria montevidensis (Cham. & Schltdl.) Kuntze, Salvinia auriculata (Aubl.) and Urochloa arrecta (Hack. & Schinz) Morrone & Zuloaga). The remaining fractions were used for the extraction of humic acid (HA) and fulvic acids (FA), which were quantified on carbon basis (controlled combustion and infrared detection). FA and HA variations were adjusted to a 1st order kinetic model. Regardless of the kind of macrophyte and trophic status, the particulate detritus showed a reactive fraction (RPOC) related to the formation of humic substances (HS) and a fraction not involved with such formations, the humin (HU); FA predominated as the main constituent of HS and their mineralization rate constants were higher than those of HA, indicating greater contribution and rapid cycling of FA. HA represented the maintenance of carbon pool. The fraction HU indicated that, depending on the detritus quality, carbon is immobilized carbon (e.g. S. auriculata) and is not readily available to cycling in aquatic environments. The trophic status along with the quality of detritus influenced the mineralization rates, especially for floating species (P. stratiotes, E. crassipes and S. auriculata) and amphibious (U. arrecta); the effects were lower in decomposition of S. montevidensis. The eutrophic environment (Vigario Reservoir) improved the mineralization over humification.